2009
DOI: 10.1002/ajpa.21127
|View full text |Cite
|
Sign up to set email alerts
|

Body size estimation of small‐bodied humans: Applicability of current methods

Abstract: Body size (stature and mass) estimates are integral to understanding the lifeways of past populations.Body size estimation of an archaeological skeletal sample can be problematic when the body size or proportions of the population are distinctive. One such population is that of the Holocene Later Stone Age (LSA) of southern Africa, in which small stature (mean femoral length = 407 mm, n = 52) and narrow pelves (mean bi-iliac breadth = 210 mm, n = 50) produce a distinctive adult body size/shape, making it diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 61 publications
3
39
0
Order By: Relevance
“…Some individuals in the North African (females, 1 out of 20; males, 3 out of 28) and Danish (females, 3 out of 10; males, 1 out of 9) samples are missing tibia; femora-only formula were used in these cases. Kurki et al (2010) found that Apex of S5 to transverse ridge of ischial tuberosity (K) Outlet anterior Transverse ridge of ischial tuberosity to dorsomedial inferior pubis (K) Canal depth Apex of auricular surface to transverse ridge of ischial tuberosity (M) a Measurement definitions are from Tague (1989), Franciscus and Holliday (1992), and Buikstra and Ubelaker (1994). Body mass was calculated following Auerbach and Ruff (2004) using the average of three femoral head diameter 1 formulae (Ruff et al, 1991;McHenry, 1992;Grine et al, 1995) for all except the small-bodied samples-the Andaman Islands, African Pygmy, Philippine, and South African samples-for which only McHenry's (1992) formula was used (Supporting Information Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…Some individuals in the North African (females, 1 out of 20; males, 3 out of 28) and Danish (females, 3 out of 10; males, 1 out of 9) samples are missing tibia; femora-only formula were used in these cases. Kurki et al (2010) found that Apex of S5 to transverse ridge of ischial tuberosity (K) Outlet anterior Transverse ridge of ischial tuberosity to dorsomedial inferior pubis (K) Canal depth Apex of auricular surface to transverse ridge of ischial tuberosity (M) a Measurement definitions are from Tague (1989), Franciscus and Holliday (1992), and Buikstra and Ubelaker (1994). Body mass was calculated following Auerbach and Ruff (2004) using the average of three femoral head diameter 1 formulae (Ruff et al, 1991;McHenry, 1992;Grine et al, 1995) for all except the small-bodied samples-the Andaman Islands, African Pygmy, Philippine, and South African samples-for which only McHenry's (1992) formula was used (Supporting Information Table S3).…”
Section: Methodsmentioning
confidence: 99%
“…New methods of estimating stature are being published regularly with higher levels of precision for a chronologically and geographically diverse array of samples, including native North Americans (Auerbach and Ruff, 2010), ancient Egyptians (Raxter et al, 2008), and late Pleistocene and Holocene Europeans (Meiklejohn and Babb, 2011;Ruff et al, 2012). Extensive research has been conducted in Africa (Raxter et al, 2008;Kurki et al, 2010;Pfeiffer and Harrington, 2011), the Americans (Auerbach, 2011;Pomeroy and Stock, 2012), East Asia (Temple et al, 2008) and Europe (Meikeljohn and Babb, 2011;Ruff et al, 2012), for example. Although interest in research on stature and body mass is rapidly expanding in many regions of the world, this focus of research is unevenly distributed across the globe.…”
mentioning
confidence: 99%
“…Adult postcranial ditnensions are consistently small throughout the Holocene. When four approaches to stature estimation from the skeleton were compared (Kurki et al 2010), results of all methods were similar to the mean statures of living Kalahari men and women (men, 160.9 cm; women, 150.1 cm; Truswell and Hanson 1976). When plotted by uncalibrated radiocarbon dates, estimated statures are within this range throughout the Holocene, except for those of a number of exceptionally short adults who lived within a period from ca.…”
mentioning
confidence: 80%